2021
DOI: 10.3390/nano11051112
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic ZnFe2O4 Nanoparticles-Reduced Graphene Oxide-Polyurethane Resin Based Nanocomposites for Electromagnetic Interference Shielding Application

Abstract: Superparamagnetic ZnFe2O4 spinel ferrite nanoparticles were prepared by the sonochemical synthesis method at different ultra-sonication times of 25 min (ZS25), 50 min (ZS50), and 100 min (ZS100). The structural properties of ZnFe2O4 spinel ferrite nanoparticles were controlled via sonochemical synthesis time. The average crystallite size increases from 3.0 nm to 4.0 nm with a rise of sonication time from 25 min to 100 min. The change of physical properties of ZnFe2O4 nanoparticles with the increase of sonicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 95 publications
(116 reference statements)
0
16
0
Order By: Relevance
“…Also, other authors observed a nonlinear behavior of the susceptibility imaginary part with the frequency that can cause the nonconstant response of the ILP. 93–95 For all samples except Fe_SA-P188, the maximum ILP is reached at the maximum frequency. For Fe_SA-P188, in contrast, 639 kHz is the most efficient frequency.…”
Section: Resultsmentioning
confidence: 86%
“…Also, other authors observed a nonlinear behavior of the susceptibility imaginary part with the frequency that can cause the nonconstant response of the ILP. 93–95 For all samples except Fe_SA-P188, the maximum ILP is reached at the maximum frequency. For Fe_SA-P188, in contrast, 639 kHz is the most efficient frequency.…”
Section: Resultsmentioning
confidence: 86%
“…The distinctive XRD peaks assigned to crystalline planes (220), (311), (400), ( 422), ( 511), (440), and (533) which confirmed the cubic spinel structure with the Fd3m space group symmetry for both ZnFe2O4 and CoFe2O4 nanoparticles [9]. Moreover, the crystallite size was calculated by debye Scherrer's formula [7], which was found to be 3.45 nm and 11.13 nm for ZnFe2O4 and CoFe2O4 nanoparticles, respectively. Further, The XRD investigation of ZnFe2O4 -rGO-TPU and CoFe2O4 -rGO-TPU nanocomposites displayed in Figure 1 (b), which reveals the presence of the diffraction planes (220), (311), (400), (422), (511), and (440) associated with the face-centered cubic structure of spinel ferrites.…”
Section: Structural Studymentioning
confidence: 74%
“…Further, the value of coercivity Hc ≈ 36.17 Oe and remanent magnetization Mr 3.37emu/g, for CoFe2O4 nanoparticles revealing its ferromagnetic behavior. However, the value of coercivity Hc ≈ 0 Oe and remanent magnetization Mr ≈ 0 emu/g for ZnFe2O4 nanoparticles, proves superparamagnetic characteristics [7]. (a-c) displays the SET, SEA, and SER of ZnFe2O4 -rGO-TPU and CoFe2O4 -rGO-TPU nanocomposites with a thickness of 0.80 mm in the frequency range of 8.2 to 12.4 GHz.…”
Section: Magnetic Studymentioning
confidence: 84%
See 2 more Smart Citations